Contributions to comply with legal and ethical aspects in research - Oyola-García, Alfredo Enrique (2017)
Mr. Editor All research - experimental or non-experimental - must include 'respect for people, beneficence, non-maleficence and justice'. Even the former advocates respect for the autonomy and protection of people with impaired or affected autonomy. Likewise, in Peru, every person has the right to personal and family privacy (Political Constitution of Peru, 1993), so providing or disclosing, by any means, information related to the medical act for academic or scientific research purposes could have Legal responsibility when this information - obtained from the medical history - is not recorded anonymously (General Health Law, 1997). Furthermore, it is prohibited to publish the identity or image of the children or adolescents involved as victims, perpetrators, participants or witnesses of an infraction, misdemeanor or crime, through the media (Code of Children and Adolescents, 2000) .